Oral manifestations of Crohn's disease. - P Asquith; Rachel Thompson; W. T. Cooke (1975)
In a systematic study of 100 patients with Crohn's disease, 100 with ulcerative colitis, and of 100 normal subjects matched for age, sex, and denture status, nine patients with Crohn's disease, two with ulcerative colitis, and one normal control were found to have oral lesions. In Crohn's disease, the macroscopic and histological appearances resembled those encountered elsewhere in the gastrointestinal tract and their incidence was related to the activity of the disorder. The lesions in the other two groups were different macroscopically and histologically. Production of salivary IgA was found to be reduced in Crohn's patients with active bowel disease. It is suggested that the occurrence of oral lesions in patients with Crohn's disease might represent a local immunological reaction to oral antigens.